2005
DOI: 10.1002/cne.20421
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic innervation of the direct and indirect basal ganglia pathways in the rat: Ipsi- and contralateral projections

Abstract: The present study describes the thalamic innervation coming from the rat parafascicular nucleus (PF) onto striatal and subthalamic efferent neurons projecting either to the globus pallidus (GP) or to the substantia nigra pars reticulata (SNr) by using a protocol for multiple neuroanatomical tracing. Both striatofugal neurons targeting the ipsilateral SNr (direct pathway) as well as striatal efferent neurons projecting to the ipsilateral GP (indirect pathway) were located within the terminal fields of the thala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 83 publications
(104 reference statements)
2
62
1
Order By: Relevance
“…Disruption in this neural system could lead to failure in selecting an alternative response and instead lead to continually executing the same, now inappropriate, response pattern. Although the experimental findings suggest that the prelimbic cortex interacts with both the subthalamic nucleus and dorsomedial striatum to facilitate cue-guided behavioral switching, this does not rule out that the prelimbic cortex, or other prefrontal cortex areas, are functionally connected with other basal ganglia areas, i.e., the nucleus accumbens (Floresco et al 2006a) or intralaminar thalamic nuclei (Canteras et al 1990;Castle et al 2005;Brown et al 2010) to also enhance cue-guided behavioral switching. Future studies can more fully determine the network of brain areas that support cue-guided behavioral switching.…”
Section: Discussionmentioning
confidence: 87%
“…Disruption in this neural system could lead to failure in selecting an alternative response and instead lead to continually executing the same, now inappropriate, response pattern. Although the experimental findings suggest that the prelimbic cortex interacts with both the subthalamic nucleus and dorsomedial striatum to facilitate cue-guided behavioral switching, this does not rule out that the prelimbic cortex, or other prefrontal cortex areas, are functionally connected with other basal ganglia areas, i.e., the nucleus accumbens (Floresco et al 2006a) or intralaminar thalamic nuclei (Canteras et al 1990;Castle et al 2005;Brown et al 2010) to also enhance cue-guided behavioral switching. Future studies can more fully determine the network of brain areas that support cue-guided behavioral switching.…”
Section: Discussionmentioning
confidence: 87%
“…There are no data available about the anti-parkinsonian action of the Pf lesion in the rat, but a recent study showed no significant persistent motor improvement after CM/Pf lesion in the MPTP monkey model of PD (Lanciego et al, 2008). This lack of effect could be due to the fact that the CM/Pf lesion was performed unilaterally in a bilateral dopaminergic lesion model, whereas crossed projections from CM/Pf to STN and SNr have been reported (Marini et al, 1999;Castle et al, 2005). Another explanation is that reversal of the response to the dopamine lesion in SNr is a requisite for efficient beneficial action on forelimb akinesia.…”
Section: Effects Of Pf-hfs Versus Lesionmentioning
confidence: 99%
“…Both direct and indirect pathway MSNs have been shown to receive synaptic input from the cortex (Somogyi et al, 1981;Hersch et al, 1995;Lei et al, 2004). Light microscopic studies have suggested that the same is true for thalamostriatal afferents (Lanciego et al, 2004;Castle et al, 2005). Electron microscopic studies in primates have suggested that afferents from the centromedian nucleus (CM) of the thalamus preferentially innervate direct pathway MSNs (Sidibé and Smith, 1996).…”
Section: Introductionmentioning
confidence: 99%